Aleiodes (Hymenoptera, Braconidae, Rogadinae) diversity in Washington U.S.A. including three new species - Fortier, Joseph (Zootaxa, 2021)
Aleiodes Wesmael is a large cosmopolitan genus of endoparasitoid wasps that is evidently especially speciose in the Western Hemisphere based on numbers of described species. As with most diverse insect groups, relatively little is known about Aleiodes species diversity and biology. Here I summarize what is known about Aleiodes diversity in Washington State and contiguous Inland Northwest states and province, and I report three new species recently collected by malaise trap sampling for Aleiodes in Okanogan County, WA: Aleiodes khalafi, Aleiodes okanoganensis, and Aleiodes quasiburrus. Given the number of new species (three) and first records of previously described species (two) in Washington elucidated by this study, there is evidently much work to do to reach a fair estimate of Aleiodes species diversity in the Inland Pacific Northwest.